48.0k views
4 votes
If K is the midpoint of JL, JK = 8x+11 and KL = 14x-1, find JL.

1 Answer

3 votes

Explanation:

Since, K is the midpoint of JL.


\therefore \: JK = KL \\ 8x + 11 = 14x - 1 \\ 11 + 1 = 14x - 8x \\ 12 = 6x \\ (12)/(6) = x \\ 2 = x \\ \\ \because \: JL = JK + KL \\ \therefore \: JL = 8x + 11 + 14x - 1 \\ \therefore \: JL = 8x + 14x + 11 - 1 \\ \therefore \: JL = 22x + 10\\ \therefore \: JL = 22 * 2 + 10..(plug \: x = 2) \\ \therefore \:JL = 44 + 10 \\ \huge \red{ \boxed{\therefore \:JL = 54}}

User SoCo
by
7.3k points